Hubungan Antara Risiko Kecelakaan Kerja Dengan Beban Kerja Di PT. X - Suci Amaliah (Jurnal Migasian, 2022)
Risk in the workplace is an embodiment of potential hazards, potential hazards as risk of work accidents in the company are including the work load. In general, work load is influenced by various very complex factors, including physical works such as the workplace, work facilities and work attitudes. In addition, work organization can also affect the workload, such as the length of work time, rest periods, shift work, night work and the wage system. The existence of an excess load can affect the workers for the occurrence of work accidents. This study uses an analytical study method with a cross-sectional approach, which purposes to determine the relationship between work load and the risk of work accidents at PT. X. The population of the study is the production department, with a sample of 81. The analysis is conducted to test and explain the relationship between work load and work accidents using the chi-square test (X2) with 95% Confident Interval (CI) or α = 0,05 which added in the SPSS software. Based on the chi-square statistical test, the p-value is 0.039 which indicates that the p-value < α (0.05) which means that there is a relationship between work load and the risk of work accidents at PT. X.